Graphene oxide influence on selected properties of polymer fuel cells based on Nafion. (1st June 2017) - Iwan, Agnieszka; Caballero-Briones, Felipe; Malinowski, Marek; Filapek, Michal; Tazbir, Igor; Guerrero-Contreras, Jesus; Kamaraj, Sathish-Kumar
Abstract: Graphene oxide (GO) was used as an additive to the anode, to modify the electrochemical properties of polymer fuel cells (PEMFC) based on Nafion. GO was obtained by modified Hummers method and fully characterized by Raman, FTIR, X-ray, TEM, electrochemically (CV) and Surface Area and Porosity Analyzer. PEMFC with a GO-based anode containing about 30% less Pt, was constructed and compared with a cell with standard anodes. The electrodes were electrochemically tested at 25 and 60 °C. A maximum power density of 134 mW/cm 2 with a current density of 374 mA/cm 2 was achieved for PEMFC with GO-based anode at 60 °C. The electrochemical surface area (ECSA) of the PEMFC with GO-based anode was about two times higher than that of the reference device. The electrochemical characterization as well as the Brunauer–Emmett–Teller (BET) and Barrett–Joyner–Halenda (BJH) analysis indicate that GO in the anode reduced Pt agglomeration, as a consequence of the increased surface area and decreased average pore width, compared with the reference electrode. Well-fitted equivalent circuits were proposed and discussed after an electrochemical impedance spectroscopy study of the constructed devices. Graphical abstract: Highlights: We constructed polymer fuel cells with graphene oxide (GO). We analyse electrical properties of PEMFC in the level of decrease Pt amount in anode. We used BET and BJH analysis to indicate that GO reduced Pt agglomeration. We analyze electrochemical properties of PEMFC by impedance spectroscopy.